Research design & method selection : making good choices in the social sciences - Panke, Diana (London : SAGE Publications Ltd., 2018)
Heavily grounded in helping students make the best choices for their projects, this book explores how to develop and work with theory, research questions, and method selection to build solid, logical proposals and move from research concepts to fully realized designs. Rather than rushing initial planning stages or reverse engineering questions from preferred methods, it encourages students to challenge unconscious biases around method selection and analysis and provides step-by-step guidance on choosing a method that is in-line with the question being explored. Focused on the role of the researcher within research design, it stresses the need to consider the theoretical underpinnings of research and not just practical issues when designing a project. It provides a sophisticated toolkit to understand: - The critical issues associated with both qualitative and quantitative methods - The approach that works best for specific research questions - How design choices can affect practice. Perfect for upper undergraduate and postgraduate students, this book will instil confidence and good decision making to ensure constructively informed design and practice.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Social sciences -- Research -- Methodology